Analisis Senyawa Metabolit Sekunder dari Ekstrak Daun Mengkudu (Morinda Citrifolia L.) serta Uji Aktivitas Antibakteri dan Antijamurnya - Norman Ferdinal; Miftahul Jannah; Afrizal (Jurnal Kimia Unand, 2025)
Noni is one of the medicinal plants that thrives in Indonesia and used as a traditional medicine. Noni leaf extract is widely reported to possess bioactivities such as antioxidant, anti-inflammatory, and antimicrobial properties. In this study, the extraction of noni leaves was carried out using a multistage maceration method with hexane, ethyl acetate, and methanol as solvents. The extracts were identified for their secondary metabolites and tested for antibacterial activity against S. aureus and E. coli, then antifungal activity against C. albicans using the disc diffusion method. The results showed that the hexane extract contained secondary metabolites including alkaloids, steroids, and coumarins, while the ethyl acetate and methanol extracts contained phenolics, flavonoids, alkaloids, steroids, and coumarins. In antibacterial testing, the three extracts exhibited varying potency against the test bacteria, with hexane extract showed the best results against S.aureus bacteria with an inhibition zone of 14.5 mm and ethyl acetate extract against E.coli bacteria with an inhibition zone of 10.28 mm. In antifungal testing, only ethyl acetate extract had an antifungal activity with an inhibiton zone of 9,77 mm.